Associations between self‐reported periodontal disease and nutrient intakes and nutrient‐based dietary patterns in the UK Biobank. (1st March 2022) - Watson, Sinead; Woodside, Jayne V.; Winning, Lewis; Wright, David M.; Srinivasan, Murali; McKenna, Gerald
Abstract: Aim: To examine the cross‐sectional associations between single nutrient intakes and posteriori nutrient‐based dietary patterns and periodontal disease risk in a subset of the UK Biobank cohort. Materials and Methods: Dietary data were collected by 24‐h dietary recall on up to five separate occasions over 16 months. A touchscreen questionnaire was used to collect oral health information. Participants were considered at high risk of periodontal disease if they reported having painful gums and/or bleeding gums and/or loose teeth. Principal component analysis identified four nutrient‐based dietary patterns from 20 nutrients. Logistic regression was used to estimate the odds ratio of periodontal disease risk for single nutrients and nutrient‐based dietary patterns. Results: A total of 9476 participants (mean age 56.2 years [SD 8.0]) were included in the analysis. Higher intakes of vitamin B6, B12, C, and E, folate, iron, potassium, magnesium, polyunsaturated fatty acids, and total sugar were associated with a lower risk of periodontal disease. Higher intake of saturated fat was associated with an increased risk. A dietary pattern characterized by high micronutrients and fibre intake was associated with low risk of periodontal disease. Conclusion: Within this sample of middle‐aged and older adults, a "high micronutrient and fibre" dietary pattern was associated with reduced risk of periodontal disease.